Which diseases are risk factors for developing gastroesophageal reflux disease? - Akyüz, Filiz; Mutluay Soyer, Özlem (Turkish Journal of Gastroenterology, 2017)
Abstract Although the pathophysiology of gastroesophageal reflux disease (GERD) remains unclear, it is accepted as a multifactorial disease. It is thought that some of the interventions that might cause alterations in the normal gastrointestinal tract anatomy and diseases that affect the lower esophageal sphincter, esophageal clearance, and stomach motility (gastric emptying) might lay a foundation for GERD development. Moreover, it is common knowledge that GERD might cause various extraesophageal symptoms and complications. A possible connection between GERD and sarcoidosis, amyloidosis, hypothyroidism, rheumatoid arthritis, mixed connective tissue disorders, Sjögren’s syndrome, systemic sclerosis, diabetes mellitus, cholecystectomy, sleeve gastrectomy, sleep apnea syndrome, chronic obstructive pulmonary disease, and asthma were summarized in this literature review. Cite this article as: Akyüz F, Mutluay Soyer Ö. Which diseases are risk factors for developing gastroesophageal reflux disease? Turk J Gastroenterol 2017;28(Suppl 1); S44-S47 Full Text Turkish